1993
DOI: 10.1002/ar.1092350407
|View full text |Cite
|
Sign up to set email alerts
|

Stage‐Dependent changes in spermatogenesis and sertoli cells in relation to the onset of spermatogenic failure following withdrawal of testosterone

Abstract: Rapid and complete withdrawal of intratesticular testosterone was achieved via the destruction of all Leydig cells with the specific Leydig cell cytotoxin ethane dimethanesulphonate (EDS). Restoration of testosterone levels was accomplished by administration of a single dose (25 mg) of testosterone esters (T) known to reverse the antispermatogenic effects of androgen withdrawal. Quantitation of the degenerating germ cells in cross sections of seminiferous tubules (ST) at stages IV-V, VII, IX, and X-XI of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 28 publications
11
72
2
Order By: Relevance
“…Some rat-based studies have demonstrated that Sertoli cells require high levels of testicular testosterone to support spermatogenesis [43][44][45]. Testosterone is known to preferentially induce conversion of round spermatids between stages VII and VIII [46][47][48][49], and this coincides with the maximal immunoexpression of AR protein in Sertoli cells [50]. In the present study, the percentage of stage IV seminiferous tubules was increased in the DES 1.5 group at 6 weeks of age.…”
Section: Discussionsupporting
confidence: 69%
“…Some rat-based studies have demonstrated that Sertoli cells require high levels of testicular testosterone to support spermatogenesis [43][44][45]. Testosterone is known to preferentially induce conversion of round spermatids between stages VII and VIII [46][47][48][49], and this coincides with the maximal immunoexpression of AR protein in Sertoli cells [50]. In the present study, the percentage of stage IV seminiferous tubules was increased in the DES 1.5 group at 6 weeks of age.…”
Section: Discussionsupporting
confidence: 69%
“…As with Gnrh-null mice, androgen or LH replacement leads to qualitative recovery of spermatogenesis in hypophysectomized rats while FSH has little direct stimulatory effect on spermatogenesis (El Shennawy et al, 1998;Elkington and Blackshaw, 1974;Russell and Clermont, 1977). Similar results are seen in response to suppression of Gnrh activity (Szende et al, 1990), and destruction of Leydig cells with the Leydig-specific cytotoxin EDS (Kerr et al, 1993;Sharpe et al, 1990).…”
Section: Introductionmentioning
confidence: 90%
“…The complexity of these interactions, many of which are still poorly understood, makes investigation of toxicological mechanisms very difficult but the specificity of some of the chemically induced lesions have been used to examine the physiological interactions between one cell type and another. In particular, 2-methoxyethanol and ethane dimethane sulphonate have been widely used to elucidate paracrine regulation (5,38,42,55).…”
Section: Spermatogenesismentioning
confidence: 99%